2015
DOI: 10.1016/j.jff.2015.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Di and tripeptides from marine sources can target adipogenic process and contribute to decrease adipocyte number and functions

Abstract: International audienceThe effect of 11 marine-derived cryptides was investigated on proliferation, differentiation and maturation of human white pre-adipocytes (HWP). They were all formerly identified as potent Angiotensin-Converting-Enzyme inhibitors.Val-Trp (VW),Val-Tyr (VY), Lys-Tyr (KY), Lys-Trp (KW), Ile-Tyr (IY), Ala-Pro (AP),Val-Ile-Tyr (VIY), Leu-Lys-Pro (LKP), Gly-Pro-Leu (GPL),Ala-Lys-Lys (AKK) and Val-Ala-Pro (VAP) were previously found in fish products and co-products as well as other marine resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The amount of peptides with a molecular weight of 200-1000 g/mol (comprising peptides with approximately 2-5 amino acids) were similar in the two fish protein hydrolysates, and none of the diets contained measurable amounts of long-chain n-3 PUFA. Both herring and salmon hydrolysates tested in the present study contained motifs with reported hypocholesterolemic and/or antidiabetic effects (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) . To our knowledge, this is the first study testing dietary hydrolysed fish protein with identified bioactive motifs with hypocholesterolemic and antidiabetic activities in obese rats.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The amount of peptides with a molecular weight of 200-1000 g/mol (comprising peptides with approximately 2-5 amino acids) were similar in the two fish protein hydrolysates, and none of the diets contained measurable amounts of long-chain n-3 PUFA. Both herring and salmon hydrolysates tested in the present study contained motifs with reported hypocholesterolemic and/or antidiabetic effects (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) . To our knowledge, this is the first study testing dietary hydrolysed fish protein with identified bioactive motifs with hypocholesterolemic and antidiabetic activities in obese rats.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, hypocholesterolemic motifs have been found in fish: HIRL and IIAEK have been found in residual material from herring (26) . When searching for known motifs with hypocholesterolemic and/or antidiabetic effects (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) in our herring and salmon hydrolysates, we found the antidiabetic motifs IPI, GPL and VW and the combined antidiabetic and hypocholesterolemic PGPL in both hydrolysates. In addition, we found the hypocholesterolemic motif IIAEK and the antidiabetic motifs GPAE and LPGP only in herring.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As peptides which exhibit DPP-4 inhibitory activity have also often displayed anti-oxidant activity, [74,75] this antioxidant effect could also play a cytoprotective effect on pancreatic beta cells. [76] Furthermore, Ben Henda et al [77] showed some diand tri-peptides derived from collagen had anorexigenic benefits by up to 80% cytotoxicity in white adipose cells, which is the type of tissue understood to be the primary source of many adipokines involved in the chronic low-grade inflammation associated with obesity. [78] However, very often the authors did not specify which specific marine source the peptides were derived from, thus it could not be included in the tablature associated with this review.…”
Section: Isolation Of Bioactive Peptides From Fish Protein Hydrolysatesmentioning
confidence: 99%
“…Alcalase hydrolysate enhanced the percentage of CD4+ and CD8+ cells in spleen. Henda et al (2015) have investigated effects of previously known peptides on proliferation, differentiation and maturation of human white pre-adipocytes. They indicated that adipocytes can be affected in different stages of their life cycle by some marine peptides but this is not correlated with their inhibiting ability on ACE (Angiotensin Converting Enzyme).…”
Section: Novel Peptidesmentioning
confidence: 99%